Inequities in the incidence and safety of abortion in Nigeria - Caroline Moreau; Mridula Shankar; Suzanne O Bell; Elizabeth Omoluabi; Funmilola OlaOlorun (BMJ Global Health)
Background We know little about the frequency, correlates and conditions under which women induce abortions in Nigeria. This study seeks to estimate the 1-year induced abortion incidence and proportion of abortions that are unsafe overall and by women’s background characteristics using direct and indirect methodologies.Methods Data for this study come from a population-based, nationally representative survey of reproductive age women (15–49) in Nigeria. Interviewers asked women to report on the abortion experiences of their closest female confidante and themselves. We adjusted for potential biases in the confidante data. Analyses include estimation of 1-year induced abortion incidence and unsafe abortion, as well as bivariate and multivariate assessment of their correlates.Results A total of 11 106 women of reproductive age completed the female survey; they reported on 5772 confidantes. The 1-year abortion incidence for respondents was 29.0 (95% CI 23.3 to 34.8) per 1000 women aged 15–49 while the confidante incidence was 45.8 (95% CI 41.0-50.6). The respondent and confidante abortion incidences revealed similar correlates, with women in their 20s, women with secondary or higher education and women in urban areas being the most likely to have had an abortion in the prior year. The majority of respondent and confidante abortions were the most unsafe (63.4% and 68.6%, respectively). Women aged 15–19, women who had never attended school and the poorest women were significantly more likely to have had the most unsafe abortions.Conclusion Results indicate that abortion in Nigeria is a public health concern and an issue of social inequity. Efforts to expand the legal conditions for abortion in Nigeria are critical. Simultaneously, efforts to increase awareness of the availability of medication abortion drugs to more safely self-induce can help mitigate the toll of unsafe abortion-related morbidity and mortality.